Improving Problem-Solving Skills and Student Learning Outcomes Through the Problem-Based Learning Model Assisted by Cultural Branch Media in Civics Lesson Content - Pardede, Fitri Mitha Natasya Br; Hadiyanti, Agnes Herlina Dwi; Ernawati, Ernawati (Universitas Sebelas Maret, 2023)
The presence of various learning models is a tool for educators to adapt the learning process based on the demands of the times, one of which is the problem-based learning model. The problem-based learning model is deemed capable of improving problem-solving skills and student learning outcomes; as such, this research aims to determine the increase in problem-solving abilities and learning outcomes of second-grade elementary school students in Yogyakarta in civics lesson content through the problem-based learning model, assisted by cultural branch learning media. This research used the type of classroom action research (CAR). The data analysis techniques employed were qualitative and quantitative. This research also utilized data collection techniques through observation, interviews, and tests. While the subjects of this research were second-grade students, consisting of 25 students, the objects were improving problem-solving abilities and student learning outcomes using the problem-based learning model assisted by learning media. Based on the results of this research, the problem-based learning model could improve students' problem-solving skills and learning outcomes in civics learning content in the second grade of elementary schools, revealing that students' problem-solving skills increased from the pre-cycle stage by 26% to cycle 1 to 64% and then to cycle stage 2 at 78%. Students' problem-solving skills from pre-cycle to cycle 2 increased by 52%. Apart from that, the average student learning outcomes increased, where the average student learning outcomes were 50 in the pre-cycle stage, 73.2 in cycle 1, and 80 in cycle 3. From these data, it can be seen that there has been an increase in student learning outcomes.